2011
DOI: 10.1007/s10886-011-9931-6
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and Semivolatile Compounds in Gray Catbird Uropygial Secretions Vary with Age and Between Breeding and Wintering Grounds

Abstract: The uropygial secretions of some bird species contain volatile and semivolatile compounds that are hypothesized to serve as chemical signals. The abundance of secretion components varies with age and season, although these effects have not been investigated in many species. We used solid-phase microextraction headspace sampling and solvent extraction coupled with gas chromatography-mass spectrometry to detect and identify volatile and semivolatile chemical compounds in uropygial secretions of gray catbirds (Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…The uropygial gland secretes preen oil which birds spread on their feathers with their bills to clean and maintain the feathers and to manage the feather-degrading bacterial communities that populate them (Jacob and Ziswiler, 1982;Shawkey et al, 2003;Martín-Vivaldi et al, 2009. This oil also contains volatile compounds that can communicate information about the individual's species identity , sex (Soini et al, 2007;Whittaker et al, 2010), age (Shaw et al, 2011), and breeding condition (Whittaker et al, 2011), and that can even be predictive of an individual's reproductive success . Recently, we demonstrated that the darkeyed junco's uropygial gland harbors a diverse and rich bacterial community, and that several of the bacterial genera identified are known to produce volatile compounds present in junco preen oil (Whittaker and Theis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The uropygial gland secretes preen oil which birds spread on their feathers with their bills to clean and maintain the feathers and to manage the feather-degrading bacterial communities that populate them (Jacob and Ziswiler, 1982;Shawkey et al, 2003;Martín-Vivaldi et al, 2009. This oil also contains volatile compounds that can communicate information about the individual's species identity , sex (Soini et al, 2007;Whittaker et al, 2010), age (Shaw et al, 2011), and breeding condition (Whittaker et al, 2011), and that can even be predictive of an individual's reproductive success . Recently, we demonstrated that the darkeyed junco's uropygial gland harbors a diverse and rich bacterial community, and that several of the bacterial genera identified are known to produce volatile compounds present in junco preen oil (Whittaker and Theis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, there also is reason to believe that preen oil is an important social chemosignal (Hirao et al 2009;Johansson and Jones 2007), as it contains volatile compounds that may act as strong signals detectable via olfaction. Preen oil compounds exhibit sexual (Amo et al 2012;Leclaire et al 2011Leclaire et al , 2012Mardon et al 2010;Soini et al 2007;Zhang et al 2010;) and age variation (Shaw et al 2011), as well as being repeatable signatures of an individual (Mardon et al 2010;Whittaker et al 2010). Finally, preen oil compounds are also species-specific (Haribal et al 2005;Soini et al 2013;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Passeriformes is the most specious order of birds, and, more recently, several songbirds have been found to produce volatile compounds (Amo et al 2012;Haribal et al 2005;Krause and Caspers 2012;Soini et al 2007;Whittaker et al 2010;Shaw et al 2011). One passerine, the dark-eyed junco, Junco hyemalis, has been shown to exhibit seasonal (Soini et al 2007), individual, and sexual variation (Whittaker et al 2010) in preen oil chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chemical communication by birds was doubted until recent years, when several studies began to decode information contained in these chemosignals (e.g., Mardon et al, 2010;Whittaker et al, 2010;Shaw et al, 2011), and provided evidence of the ability of birds to detect these chemicals Whittaker et al, 2011) and a role of these chemicals in social and reproductive behavior (reviewed in Balthazart and Taziaux, 2009). In most species of birds studied to date, compounds that may play a role in chemical signaling are present in preen oil secreted from the uropygial, or preen, gland (Bonadonna et al, 2007;Soini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Birds spread this oil over feathers while preening, where it functions to protect the feathers from exposure to the environment, enhance insulation, and lower ectoparasite load (Jacob and Ziswiler, 1982). The volatile and semivolatile compounds in preen oil also contribute an odor to a bird, which varies qualitatively among species , and quantitatively within species, between sexes, populations, individuals (Soini et al, 2007;Mardon et al, 2010;Whittaker et al, 2010), and age classes (Shaw et al, 2011).…”
Section: Introductionmentioning
confidence: 99%